The competitive esports physiological, affective, and video dataset - Maciej Behnke; Wadim Krzyżaniak; Jan Nowak; Szymon Kupiński; Patrycja Chwiłkowska; Szymon Jęśko Białek; Maciej Kłoskowski; Patryk Maciejewski; Kacper Szymański; Daniël Lakens; Kate Petrova; Jeremy P. Jamieson; et al. (Scientific Data)
Abstract Esports refers to competitive video gaming where individuals compete against each other in organized tournaments for prize money. Here, we present the Competitive Esports Physiological, Affective, and Video (CEPAV) dataset, in which 300 male Counter Strike: Global Offensive gamers participated in a study aimed at optimizing affect during esports tournament1. The CEPAV dataset includes (1) physiological data, capturing the player’s cardiovascular responses from before, during, and after over 3000 CS: GO matches; (2) self-reported affective data, detailing the affective states experienced before gameplay; and (3) video data, providing a visual record of 552 in-laboratory gaming sessions. We also collected (affect-related) individual differences measures (e.g., well-being, ill-being) across six weeks in three waves. The self-reported affective data also includes gamers’ natural language descriptions of gaming affective situations. The CEPAV dataset provides a comprehensive resource for researchers and analysts seeking to understand the complex interplay of physiological, affective, and behavioral factors in esports and other performance contexts.